Gene expression dosage regulation in an allopolyploid fish. - I Matos; M P Machado; M Schartl; M M Coelho (PLoS ONE, 2015)
How allopolyploids are able not only to cope but profit from their condition is a question that remains elusive, but is of great importance within the context of successful allopolyploid evolution. One outstanding example of successful allopolyploidy is the endemic Iberian cyprinid Squalius alburnoides. Previously, based on the evaluation of a few genes, it was reported that the transcription levels between diploid and triploid S. alburnoides were similar. If this phenomenon occurs on a full genomic scale, a wide functional ''diploidization'' could be related to the success of these polyploids. We generated RNA-seq data from whole juvenile fish and from adult livers, to perform the first comparative quantitative transcriptomic analysis between diploid and triploid individuals of a vertebrate allopolyploid. Together with an assay to estimate relative expression per cell, it was possible to infer the relative sizes of transcriptomes. This showed that diploid and triploid S. alburnoides hybrids have similar liver transcriptome sizes. This in turn made it valid to directly compare the S. alburnoides RNA-seq transcript data sets and obtain a profile of dosage responses across the S. alburnoides transcriptome. We found that 64% of transcripts in juveniles' samples and 44% in liver samples differed less than twofold between diploid and triploid hybrids (similar expression). Yet, respectively 29% and 15% of transcripts presented accurate dosage compensation (PAA/PA expression ratio of 1 instead of 1.5). Therefore, an exact functional diploidization of the triploid genome does not occur, but a significant down regulation of gene expression in triploids was observed. However, for those genes with similar expression levels between diploids and triploids, expression is not globally strictly proportional to gene dosage nor is it set to a perfect diploid level. This quantitative expression flexibility may be a strong contributor to overcome the genomic shock, and be an immediate evolutionary advantage of allopolyploids.